Muellerius capillaris in sheep: occurrence and identification of the parasites - Gonçalves, P. Cabral; Santos, J. Oswaldo P. dos; Ueno, Hakaru (Pesquisa Agropecuaria Brasileira, 2014)
Observations carried out in Polwarth sheep reared in natural and improved pastures, indicated a high infection by Muellerius capillaris (Mueller 1889) (Nematoda: Protostrongylidae) in a large number of animals, through identification and counting of larvae in faeces. From 129 sheep, 70 were positive for first stage larvae in faeces, corresponding to 45,7% of infections. Necropsies of two sheep showed the presence of numerous small nodules, enphysema areas and a regular quantity of adult helminths.